Amino Acid Composition of Milk from Cow, Sheep and Goat Raised in Ailano and Valle Agricola, Two Localities of ‘Alto Casertano’ (Campania Region) - Nicola Landi; Sara Ragucci; Antimo Di Maro (Foods, 2021)
Cow, sheep and goat raw milk raised in Ailano and Valle Agricola territories (‘Alto Casertano’, Italy) were characterized (raw proteins, free and total amino acids content) to assess milk quality. Raw milk with the highest total protein content is sheep milk followed by goat and cow milk from both localities. Total amino acid content in cow, goat and sheep raw milk is 4.58, 4.81 and 6.62 g per 100 g, respectively, in which the most abundant amino acid is glutamic acid (~20.36 g per 100 g of proteins). Vice versa, the free amino acids content characteristic profiles are different for each species. In particular, the most abundant free amino acid in cow, sheep and goat raw milk is glutamic acid (9.07 mg per 100 g), tyrosine (4.72 mg per 100 g) and glycine (4.54 mg per 100 g), respectively. In addition, goat raw milk is a source of taurine (14.92 mg per 100 g), retrieved in low amount in cow (1.38 mg per 100 g) and sheep (2.10 mg per 100 g) raw milk. Overall, raw milk from ‘Alto Casertano’ show a high total protein content and are a good source of essential amino acids.